2013
DOI: 10.14256/jce.916.2013
|View full text |Cite
|
Sign up to set email alerts
|

Punching of column footings - comparison of experimental and calculation results

Abstract: Punching of column footings-comparison of experimental and calculation results The column punching through the slab is most often related to floor structures, and less often to foundation slabs under columns. Calculation models for these two problems are often not separated. The deficit of experimental results for column footings results in the use of floor slab models. A review of the theoretical and experimental research references, including Codes/Regulations for punching calculation of column footings, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A data base for a total of 195 specimens from the previous experimental works on column footings as collected from [1][2][3][4][5][6][7][8][9][10][11][12][13][14][26][27][28][29][30][31]. These column footings connections have a wide variety of material and geometrical features with footing dimensions ranged between (800 -3050 mm), the column widths (150 -534 mm), the footing depths (82 -760 mm), the shear slenderness ratios (0.44 -10.48), the compressive concrete strength (7.92 -47.6 MPa), the flexural reinforcement ratios (0.12% -1.77%) and the yielding strengths of steel reinforcement (289 -580 MPa).…”
Section: Experimental Tests Of Footings and Selected Design Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…A data base for a total of 195 specimens from the previous experimental works on column footings as collected from [1][2][3][4][5][6][7][8][9][10][11][12][13][14][26][27][28][29][30][31]. These column footings connections have a wide variety of material and geometrical features with footing dimensions ranged between (800 -3050 mm), the column widths (150 -534 mm), the footing depths (82 -760 mm), the shear slenderness ratios (0.44 -10.48), the compressive concrete strength (7.92 -47.6 MPa), the flexural reinforcement ratios (0.12% -1.77%) and the yielding strengths of steel reinforcement (289 -580 MPa).…”
Section: Experimental Tests Of Footings and Selected Design Codesmentioning
confidence: 99%
“…Numerous experimental and analytical studies had been conducted to investigate the punching shear capacity of footings and calibrate the various national and international design codes [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. For the literature review, it was found that: (1) all selected design codes provide conservative estimates for the punching shear capacity of slender R.C.…”
Section: Introductionmentioning
confidence: 99%
“…Punching investigation of the footing rested on real soil was done in practice only by using a sandbox test system to simulate soil effects and sand density, with the latter factor being a variable ranging from loose to dense [4][5][6]. Later on, similar experiments were conducted using a mixture of river sands [7]. Other studies were also carried out to investigate the punching shear of slabs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The contact stress distribution beneath RC Footings resting on soil depends on the type of soil, as well as the stiffness of the footing [1]. Previous research regarding strengthening of existing RC Footing has focused on improving punching and shear behavior [2][3][4][5]. In 2017, Gia Toai Truong [2] investigated the effects of inclined shear reinforcement, highstrength concrete, and additional concrete cast with amorphous metallic fibers (AMFs) on the punching capacity of existing footings, the authors stated that the effect of AMFs and high strength concrete on punching resistance was higher than the effect of using inclined shear reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also developed a design model for assessing punching strength using the soil-structure interaction, and it was found that the contact stress distribution beneath the rigid footings rested on sand was higher at the center of the footing and lower at edges. In 2013, Bonic and Folic [4] studied the punching behavior on RC footings, subjected to concentric loading, resting on sand. This study showed that the actual punching failure load was higher than the expected failure load, calculated according to the international ASTESJ ISSN: 2415-6698 codes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%